Ocena stanu jakości wody w rzece Obrzycy = Water quality evaluation of the Obrzyca river - Jakubaszek, Anita; Myszograj, Sylwia; Płuciennik-Koropczuk, Ewelina; Zimna, Karolina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the results of the basic physical and chemical indicators of water quality in the upper and lower reaches of the river Obrzyca. Assessment of water quality is important because of located at the estuary part of the river water intake surface for Zielona Góra. The water from the initial reaches has been qualified to III class of water quality based on the achieved results.
Keywords: jakość wody; Obrzyca; water quality; Obrzyca river